2020
DOI: 10.1109/tii.2019.2958826
|View full text |Cite
|
Sign up to set email alerts
|

PGA-Net: Pyramid Feature Fusion and Global Context Attention Network for Automated Surface Defect Detection

Abstract: Surface defect detection is a critical task in industrial production process. Nowadays, there are lots of detection methods based on computer vision and have been successfully applied in industry, they also achieved good results. However, achieving full automation of surface defect detection remains a challenge, due to the complexity of surface defect, in intra-class, while the defects between inter-class contain similar parts, there are large differences in appearance of the defects. To address these issues, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
104
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(113 citation statements)
references
References 46 publications
0
104
0
9
Order By: Relevance
“…After the model was tested on the Northeastern University (NEU) surface defect dataset, the F measure was 0.606, and the calculation time on each image was 0.713 s. Yan et al [ 95 ] developed a probabilistic saliency framework based on a feature enhancement mechanism for realizing robust defect detection on a micro 3D texture surface of industrial products, which designed the absolute strength deviation and local strength aggregation to represent the initial saliency of the pixel level while all pixels are classified as defective or non-defective. To address the issues of intra-class defects having large differences in appearance while inter-class defects contain similar parts, Song et al have studied many approaches to combine visual salience with other ideas, such as Encoder–Decoder Residual network (EDRNet) [ 96 ], multiple constraints and improve texture feature (MCITF) [ 97 ], attention mechanism [ 98 ], and pyramid feature (PGA-Net) [ 99 ], and the experimental results show that they are both effective and outperform the state-of-the-art methods. The advantages of introducing visual saliency are mainly manifested in two aspects: first, limited computing resources are allocated to more important information in images and videos; second, the results of introducing visual saliency are more in line with people’s visual cognition needs.…”
Section: Taxonomy Of Two-dimension Defect Detection Methodsmentioning
confidence: 99%
“…After the model was tested on the Northeastern University (NEU) surface defect dataset, the F measure was 0.606, and the calculation time on each image was 0.713 s. Yan et al [ 95 ] developed a probabilistic saliency framework based on a feature enhancement mechanism for realizing robust defect detection on a micro 3D texture surface of industrial products, which designed the absolute strength deviation and local strength aggregation to represent the initial saliency of the pixel level while all pixels are classified as defective or non-defective. To address the issues of intra-class defects having large differences in appearance while inter-class defects contain similar parts, Song et al have studied many approaches to combine visual salience with other ideas, such as Encoder–Decoder Residual network (EDRNet) [ 96 ], multiple constraints and improve texture feature (MCITF) [ 97 ], attention mechanism [ 98 ], and pyramid feature (PGA-Net) [ 99 ], and the experimental results show that they are both effective and outperform the state-of-the-art methods. The advantages of introducing visual saliency are mainly manifested in two aspects: first, limited computing resources are allocated to more important information in images and videos; second, the results of introducing visual saliency are more in line with people’s visual cognition needs.…”
Section: Taxonomy Of Two-dimension Defect Detection Methodsmentioning
confidence: 99%
“…The core of the model is a simple feed-forward neural network including convolutional layers and pooling layers. Dong et al [ 3 ] utilized the feature fusion and context attention strategies to address the complexity of surface defects in both intra-class and inter-class. Specifically, multi-scale features were fused by skip connections first.…”
Section: Related Workmentioning
confidence: 99%
“…With the recent advancement in deep learning, surface defect classification with deep learning-based techniques has become popular. For example, the works of [ 3 , 4 , 5 ] utilize deep learning models for surface defects classification which proves that deep learning models are far more accurate than traditional image processing-based and machine learning methods. To enhance the performance, data augmentation methods are usually utilized [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Veitch-Michaelis et al [24] studied the 3D cracks recognition method through the combination of morphological detection and SVM classifier. Hongwen Dong in Northeastern University proposed a pyramid feature fusion and a global context attention network for pixel-wise detection of surface defect in the industrial production process [25]. Fatima A. Saiz et al [26] reported a deep-learning based automatic defects recognition system in which CNN was utilized in the model design, which achieved an outstanding classification rate.…”
Section: Introductionmentioning
confidence: 99%